Analysis of Aluminium Hot Extrusion by Finite Volume Method - Bressan J.D.* (2015)
© 2015 Elsevier Ltd.A novel numerical approach to calculate strain rate, stress and velocity fields of axisymmetric hot extrusion process is presented and discussed. Traditionally, metal forming analysis has been performed by upper-bound, slab, slip-line and Finite Element (FEM) methods. However, Finite Volume Method (FVM) has been recently developed for metal plastic flow analysis. Hence, metal extrusion was modelled by flow formulation. Governing equations were discretized by FVM, using Explicit MacCormack Method in structured and collocated mesh. SIMPLE method was applied to attain necessary pressure-velocity coupling. This scheme was applied to hot extrusion of aluminium alloy 6351. Numerical results of velocity field from present FVM produced consistent and good agreement with FEM results, employing FORGE 2008. Present results also suggest that MacCormack and SIMPLE methods can be applied in the solution of metal forming processes.